Decentralization and Citizens' Participation in Local Governance: Does Trust and Transparency Matter? – An Empirical Study. Issue 2 (4th May 2021) - Arkorful, Vincent Ekow; Lugu, Benjamin Kweku; Hammond, Anastasia; Basiru, Ibrahim
Abstract: The wind of change that swept across the African continent and other developing countries ensuingly engendered the need to institute measures that would bring government to the people's doorstep. This led to the prioritization and touting of decentralization. Against the backdrop of the proximate reason to accelerate public access to government, the express expectation was that a germane space would be created to enhance participation. However, the validity of this postulation is yet to be realized. The study, therefore, set out to examine the relationship between decentralization and people's participation, with the mediating role of trust and transparency. Results of data analysis (561 respondents), using the structural equation modelling technique, established not only the appropriateness of the proposed study model, but also, the imperativeness of the trust and transparency to decentralization and participation. The implications of the study are delineated for effective policy and practice.